2021
DOI: 10.1002/anie.202103410
|View full text |Cite
|
Sign up to set email alerts
|

Bispericyclic Diels–Alder Dimerization of ortho‐Quinols in Natural Product (Bio)Synthesis: Bioinspired Chemical 6‐Step Synthesis of (+)‐Maytenone

Abstract: Many natural products of plant or microbial origins are derived from enzymatic dearomative oxygenation of 2‐alkylphenolic precursors into 6‐alkyl‐6‐hydroxycyclohexa‐2,4‐dienones. These so‐called ortho‐quinols cyclodimerize via a remarkably selective bispericyclic Diels–Alder reaction. Whether or not the intervention of catalytic or dirigent proteins is involved during this final step of the biosynthesis of these natural products, this cyclodimerization of ortho‐quinols can be chemically reproduced in the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 88 publications
(87 reference statements)
3
31
0
Order By: Relevance
“…The bisditerpenoid (+)-maytenone was prepared in an enzymatic-like two-step sequence from (+)-ferruginol (Scheme 26). 73 With the help of the Salen-type derived bisiodyl reagent ( 85 ), (+)-ferruginol was stereospecifically oxidised to dienone 84 . The latter was immediately subjected to 14 kbar pressure at r.t, and its subsequent cyclodimerization afforded the dimeric adduct as a single enantiomer in a 60% yield.…”
Section: Tandem Cycloaddition and Related Processes Under Hyperbaric ...mentioning
confidence: 99%
“…The bisditerpenoid (+)-maytenone was prepared in an enzymatic-like two-step sequence from (+)-ferruginol (Scheme 26). 73 With the help of the Salen-type derived bisiodyl reagent ( 85 ), (+)-ferruginol was stereospecifically oxidised to dienone 84 . The latter was immediately subjected to 14 kbar pressure at r.t, and its subsequent cyclodimerization afforded the dimeric adduct as a single enantiomer in a 60% yield.…”
Section: Tandem Cycloaddition and Related Processes Under Hyperbaric ...mentioning
confidence: 99%
“…166 In a recent study, Quideau and co-workers asymmetric synthesized 22 in high yield from the commercially available monomer (+)-dehydroabietylamine (22a) in a six-step reaction (Scheme 25). 167 The [4 + 2] cyclodimerization of ortho-quinols reactions catalyzed by chiral reagents is the key step in the process. Moreover, the…”
Section: Semisynthesis Of Bisditerpenoidsmentioning
confidence: 99%
“…166 In a recent study, Quideau and co-workers asymmetric synthesized 22 in high yield from the commercially available monomer (+)-dehydroabietylamine ( 22a ) in a six-step reaction (Scheme 25). 167 The [4 + 2] cyclodimerization of ortho -quinols reactions catalyzed by chiral reagents is the key step in the process. Moreover, the diastereoisomer of 22 , dimer 279 , was also synthesized in the same study, and was proved to be the bisditerpenoid identified from Harpagophytum procumbens .…”
Section: Biomimetic Syntheses Of Bisditerpenoidsmentioning
confidence: 99%
“…This work has benefited from the analytical facilities of the CESAMO platform at the University of Bordeaux. We thank B. Kauffman and S. Massip (CNRS-UMS 3033) for conducting X-ray diffraction experiments and solving the structures of compounds 4 and 20, [34] Prof.C .K.J ankowski for kindly providing us with the NMR spectra of natural 4,and Dr A. Fedotova for her kind help in the use of the high-pressure equipment. Akzeptierte Fassung online: 14.…”
Section: Acknowledgementsmentioning
confidence: 99%